The impact of green marketing strategies on the accounting performance: the moderating role of AI utilization - Hind Al-Ahmed; Khaled Alshaketheep; Ahmad Shajrawi; Ahmad Mansour; Omar Zraqat; Arafat Deeb; Lina Hussien (Heritage and Sustainable Development)
This paper seeks to discuss green marketing strategies that are becoming particularly popular as organizations strive to boost sustainability and accounting performance. As well as, exploring the moderating role of AI in green marketing strategy's impact on firms’ accounting performance (return on assets, return on equity, and profit margins). A parallel research approach was used: a survey of firms’ annual reports and content analysis of interviews with marketing managers of different companies operating in different industries. It concluded that green marketing practices, in particular the use of AI, greatly enhance the competitive performance and accounting capabilities of a company. As a powerful technology, AI can be employed to enhance green marketing practice and enable the organization to achieve sustainable growth. This research bridges the gap between sustainability and technology and demonstrates how the relationship between accounting performance and green marketing is moderated using AI in order to maintain competitor and financial advantages. This research advises organizations to emphasize being sustainable and make greater investments in AI development to improve their marketing strategy. These two concerns with sustainability and technology adoption can determine the success of organizations in the long term.